Dynamic conditional correlation analysis of financial contagion: eurodollar future and Forex bitcoin markets - Tsiaras, Konstantinos (Journal of the Belarusian State University. Economics, 2021)
This paper examines the time-varying conditional correlations between eurodollar future market and seven Forex bitcoin markets. We apply a bivariate dynamic conditional correlation DCC-GARCH model in order to capture potential contagion effects between the markets for the period 2017–2019. Empirical results reveal contagion during the under investigation period regarding the seven bivariate model, showing potential volatility transmission channels among the markets. Findings have crucial implications for policymakers, who provide regulations for the above derivative markets.
Keywords: DCC-GARCH model; bitcoin Forex markets; eurodollar future market; financial contagion; dynamic conditional correlations; динамически условная коинтеграция